Development of Learning Model Ã¢â‚¬Å“Chair Grounds RingÃ¢â‚¬Â Made from Environmentally Friendly Raw Materials - Qomarrullah, Rif'iy; Sutoro, Sutoro; Kurdi, Kurdi (Department of Physical Education, Sport, Health and Recreation, 2020)
This study aims to develop a basketball learning model with ring modification. This study uses a development model, using a sample of 350 fifth grade elementary school students in Jayapura City. This research was conducted in April to September 2019. The stages of this research were: 1) Analyzing the product, 2) Developing the product, 3) Expert validation, 4) Field trials, 5) revisions, and product results. The results of the study are: (1) Model game material for basketball chair grounds ring basketball; (2) The effectiveness of the game model can increase student physical activity, this can be seen by increasing the pulse rate before and after participating in learning basketball material. The increase in the average pulse rate of students after treatment increased by 81.7% and the maximum increase in pulse rate by 47.8%; (3) The basketball game model can overcome the limitations of existing facilities and infrastructure. The conclusion of this research is that the use of the product development model of the basketball ring tool can be used as a medium for physical education learning and has an effect on the physical activity of students in elementary school. Suggestions for physical education teachers in elementary schools to be able to use this model in schools in learning basketball games.